Hukum Zakat Terhadap Cryptocurrency Dalam Pengelolaan Harta Digital - Uljanah, Nisa; Revitalina, Yosi (Jurnal Multidisiplin Dehasen (MUDE), 2025)
In the current digital era, cryptocurrency has become an increasingly popular digital asset in the world of finance. However, the legal question surrounding the obligation of zakat on cryptocurrencies is still a significant debate among Muslims. This research aims to analyze the legal implications of zakat on cryptocurrency in the context of digital asset management. The research methodology used is qualitative, this includes analysis of Islamic legal documents, fatwas from religious authorities, as well as case studies of the use of cryptocurrency as an investment asset. The research results show that the determination of zakat obligations on cryptocurrencies is not uniform, depending on the interpretation of the school of thought and the specific conditions of its use. Several aspects that need to be considered in calculating zakat on cryptocurrency include the current rupiah exchange rate, digital asset holding period, and the type of cryptocurrency owned. Apart from that, clear guidance is also needed regarding how to calculate the zakat value of fluctuating cryptocurrencies. In relation to digital asset management, this research also highlights the security and regulations related to cryptocurrency, in digital assets. This emphasizes the need for awareness among Muslims in understanding and managing digital assets by considering aspects of zakat obligations. It is hoped that this research can provide clearer knowledge for Muslims in understanding their zakat obligations towards cryptocurrency, so that they can make a positive contribution in managing digital assets according to sharia.